The Effect of Audio Visual and Booklet to Increase Behaviour of Screening IVA Test at Sukarasa Public Health Center - Aisyah Salsabila; Agus Riyanto; Suhat; Novie E. Mauliku (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Women's health is an indicator of health achievement in the world, including in Indonesia. Cervical cancer is a female cancer that causes the most deaths due to cancer, especially in developing countries. Objective: The study aims to analyse the effect of audio-visual and booklet in education to increase behavior of screening IVA test at the Sukarasa Public Health Center Area. Method: This research used a quasi-experimental design with a pretest posttest non-equivalent control group design. Data analysis in this study used univariate analysis, bivariate analysis using paired T-test, independent T-test, Mc-Namer, chi-square and multivariate test using multiple logistic regression. Results: The results of this study show that the results of the paired T-test of knowledge have a p-value (p=0.001) in the intervention and the control (p=0.724). In the attitude category, p-value is a (p=0.001) in the intervention and the control (p=0.469) so it can be concluded that there are differences in knowledge and attitudes before and after the intervention. In the practice category using the Mc-Nemar test produced a p-value (p=0.001) in the intervention and control so that there were differences in practice before and after intervention. The results of the independent T-Test showed a p-value for knowledge (p=0.001) and attitude (p=0.001), which means there were differences after the intervention. The results of knowledge and attitudes the chi-square test show (p=0.001), which means there is a relationship between knowledge with practice, and attitude with practice. Multivariate test on knowledge of occupational confounders. In attitude there is a confounder of education, while in practice there are confounders, namely age and education. Conclusion: Audio visual and booklet can increase behaviour of screening IVA Test at the Sukarasa Community Health Center, Bandung City.